Optimization of a methodology for simultaneous determination of twelve chlorophenols in environmental water samples using in situ derivatization and continuous sample drop flow microextraction combined with gas chromatography-electron-capture detection. Issue 19 (5th May 2017) - Karimaei, Mostafa; Sharafi, Kiomars; Moradi, Masoud; Ghaffari, Hamid Reza; Biglari, Hamed; Arfaeinia, Hossein; Fattahi, Nazir
Abstract : Continuous sample drop flow microextraction (CSDFME) combined with gas chromatography-electron-capture detection (GC-ECD) has been developed as a high preconcentration technique for the determination of chlorophenols (CPs) in environmental water samples. Abstract : Continuous sample drop flow microextraction (CSDFME) combined with gas chromatography-electron-capture detection (GC-ECD) has been developed as a high preconcentration technique for the determination of chlorophenols (CPs) in environmental water samples. In this method, a few microliters of organic solvent (11.0 μL chlorobenzene) is transferred to the bottom of a conical test tube. Then 10.0 mL of aqueous solution transforms into fine droplets while passing through the organic solvent. At this stage, CPs are extracted into the organic solvent. Under the optimum conditions, enrichment factors and extraction recoveries are in the range of 630–1770 and 31.5–88.5, respectively. The calibration graphs are linear in the range of 0.01–300 μg L −1 and limits of detection (LODs) are in the range of 0.005–0.50 μg L −1 . The relative standard deviations (RSDs, for 100 μg L −1 of MCPs, 50 μg L −1 of DCPs, 2.00 μg L −1 of TCPs, 1.00 μg L −1 of TeCPs and PCP in water) with and without using an internal standard are in the range of 0.9–5.5% ( n = 7) and 1.2–6.4% ( n = 7), respectively. The relative recoveries of well, tap and river water samples which have been spiked with different levels of CPs are in the range of 90.6–104.2%.